(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
For good health, not only factors such as diet, taking care of your movements and others are necessary, but also such a key factor as physical activity. This has been proven hundreds of times; when a person constantly engages in physical exercise, he easily achieves his goal. In addition, physical activity takes us to a new level of well-being in terms of education, science and other social spheres.